A espiritualidade na contemporaneidade: uma busca do homem mergulhado em sua subjetividade - Figueira, Adriana Barata dos Santos (2014)
Currently live a culture marked by satisfaction of individual wishes. This fact has influenced many aspects of life in society, including in the field of religion. The present work investigates the human subjectivity to it, placing the man in contemporary times, immersed in the transience of relationships and attitudes, is checked as the spirituality presents itself in your life. From a rereading of the religious phenomenon and a new look about this experience that "you don't know where it comes from or where it goes," considered here according to the vision of Vannini (2005) an experience of the spirit, the religiosity enters the lives of people no longer as an illusory and misleading experience as was advocated for a long time. She goes on to meet the new demands requested by this new man.